APLIKASI METODE ASBĀB AL-NUZŪL MAKRO DALAM SURAT AL-AN’AM - Nadyya Rahma Azhari (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2023)
Abstract: Not all verses in the Qur'an have a history (asbāb al-nuzūl micro), sura al-An'am is one of them. While asbāb al-nuzūl has an important role in explaining the historicity of a verse. Even so, there have been methods to keep looking at the historical context of the verse, one of which is by bringing up the macro asbāb al-nuūl. This method has actually been discussed by several Islamic scholars, one of them is Fazlur Rahman in the double movement method. Where there is a macro situation that may have a connection with the verse. More in theory about asbāb al-nuzūl macro is developed in a book entitled The Smart Book of Sababun Nuzul from Micro to Macro an Epistemology by Mu'ammar Zayn Qadafy. In this book he describes several methods for finding the macro asbāb al-nuzul. So this paper will try to apply these methods in looking at the asbāb al-nuzūl Al-An'am and to what extent this macro asbāb al-nuzul is able to help explain its historical conditions.Keywords: Asbāb al-Nuzūl, Makro, Mikro, Al-An’am Abstrak: Tidak semua ayat dalam Al-Qur’an memiliki riwayat (asbāb al-nuzūl mikro), surat al-An’am adalah salah satunya. Sementara asbāb al-nuzūl memiliki peranan penting dalam menjelaskan historisitas suatu ayat. Meski demikian, telah ada metode untuk tetepa melihat konteks historis ayat tersebut, salah satunya dengan memunculkan asbāb al-nuūl makro. Metode ini sebenarnya sudah dibahas oleh beberapa sarjana Islam, salah satunya Fazlur Rahman dalam metode double movement. Di mana ada sebuah situasi makro yang mungkin memilki keterkaitan dengan ayat tersebut. Lebih dalam teori tentang asbāb al-nuzūl makro ini dikembangkan dalam sebuah buku berjudul Buku Pintar Sababun Nuzul dari Mikro hinngga Makro Sebuah Epistimologi oleh Mu’ammar Zayn Qadafy. Dalam  buku ini ia menjelaskan beberapa metode untuk menemukan asbāb al-nuzul makro tersebut.Maka tulisan ini akan mencoba untuk mengaplikasikan metode tersebut dalam melihat asbāb al-nuzūl Al-An’am dan sejauh mana asbāb al-nuzul makro ini mampu membantu menjelaskan kondisi historisnya. Kata Kunci: Asbāb al-Nuzūl, Makro, Mikro, Al-An’am